Practical Wisdom, Leadership and Culture: Indigenous, Asian and Middle-Eastern Perspectives - Intezari, Ali (The Practical Wisdom in Leadership and Organization Ser., 2020)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Contents -- Contributor bios -- Foreword -- Introducing Practical Wisdom, Leadership and Culture: Indigenous, Asian and Middle-Eastern Perspectives -- SECTION I The Indigenous perspective -- 1 Ecological sustainability and practical wisdom from die Maasai and Hadza people in East Africa -- 2 The wisdom of inclusion: Maori leadership and management practices that make a world of difference -- 3 The wisdom of differentiating between Indigenous leader and Indigenous leadership -- 4 Native American transplanar wisdom: a pragmatic view and application -- 5 Conceptions of wisdom in rural Uganda: a different view of what's important in life -- SECTION II The Asian perspective -- 6 Fostering contemplative and spiritual growth: revisiting Confucianism and wisdom learned from T'oegye Yi Hwang ( ) for educators -- 7 Personal wisdom as reflected in the Vietnamese classic literature The Tale of Kiê'u -- 8 On endeavor-based wisdom: an East Asian Confucian perspective in a poly-cultural world -- 9 Wisdom: a Philippine perspective -- SECTION III The Middle-Eastern perspective -- 10 Practical wisdom in Ancient Iran -- 11 The concept of wisdom in the Arab-Islamic traditions -- 12 The wisdom of good thought and deed: the Persian perspective -- Index.